The mechanisms of manual therapy: A living review of systematic, narrative, and scoping reviews. - Damian L Keter; Joel E Bialosky; Kevin Brochetti; Carol A Courtney; Martha Funabashi; Steve Karas; Kenneth Learman; Chad E Cook (PLoS ONE)
Introduction Treatment mechanisms are the underlying process or pathway through which a treatment influences the body. This includes molecular, cellular and physiological processes or pathways contributing to treatment effect. Manual therapy (MT) evokes complex mechanistic responses across body systems, interacting with the individual patient and context to promote a treatment response. Challenges arise as mechanistic studies are spread across multiple professions, settings and populations. The purpose of this review is to summarize treatment mechanisms that have been reported to occur with MT application. Methods Four electronic databases were searched (Medline, CINAHL, Cochrane Library, and PEDro) for reviews investigating mechanistic responses which occur during/post application of MT. This review was registered a priori with PROSPERO (CRD42023444839). Methodological quality (AMSTAR-2) and risk of bias (ROBIS) were assessed for systematic and scoping reviews. Data were synthesized by mechanistic domain. Results Sixty-two reviews were included. Systematic reviews (n = 35), narrative reviews (n = 24), and scoping reviews (n = 4) of asymptomatic (n = 37), symptomatic (n = 43), non-specified human subjects (n = 7) and animals (n = 7) were included. Reviews of moderate quality supported neurovascular, neurological, and neurotransmitter/neuropeptide changes. Reviews of low quality supported neuroimmunce, neuromuscular, and neuroendocrine changes. Reviews of critically low quality support biomechanical changes. Conclusions Findings support critically low to moderate quality evidence of complex multisystem mechanistic responses occurring with the application of MT. Results support peripheral, segmental spinal, and supraspinal mechanisms occurring with the application of MT, which can be measured directly or indirectly. The clinical value of these findings has not been well established. While MT has proven to be an effective intervention to treat conditions such as pain, the current body of literature leaves uncertainty as to 'why' MT interventions work, and future research should look to better define which mechanisms (or combinations of mechanisms) are mediators of clinical response.